UPAYA PERLINDUNGAN HUKUM OLEH SATUAN RESERSE NARKOBA POLRES PASAMAN TERHADAP ANAK TERSANGKA PELAKU TINDAK PIDANA - Erwin Sanra (UNES Journal of Swara Justisia, 2019)
Criminal narcotics committed by children violating the law and contrary to the values andnorms in society, protection of children is very important, considering that children are thenext generation of the nation. This requires legislation that protects children from variouscriminal acts, namely Law Number 35 of 2014 concerning Amendments to Act Number 23of 2002 concerning Child Protection and Law Number 35 of 2009 concerning Narcotics.The purpose of this law itself is to protect children's rights from all kinds of actions.Children are someone who is in a period of growing and developing, Handling of childrenwho face legal problems in this case facing the problem of distributing narcotics must bedone by prioritizing the best interests for the child. The number of cases of narcotics abusetoday is increasingly troubling our lives, narcotics which are now no longer looking atage, ranging from children, adolescents to parents can be included in this drug abuse trap.And like the case that happened in Pasaman where there were children who committednarcotics crime and sought to be given protection for the child. Based on the results of thediscussion and analysis, it can be concluded that: First, the legal protection of childrensuspected of narcotics crime in Pasaman District Police Station is carried out by the childinvestigator of Pasaman District Police, accompanied by social counselor (PK) and whenthe investigation is made, the case is adjusted accordingly, not exposing the case to themedia, in his examination accompanied by a lawyer, presenting Bapas and attempting thechild not to be arrested but obliged to report, Second Constraints encountered in the effortto provide legal protection to the child of the suspect in the Narcotics crime at thePasaman Police Station are the limitations of child investigators who have Inauguration isstill reduced and the lack of facilities and infrastructure such as child detention is notavailable, the Bapas office is far away, namely in Bukittinggi so it is difficult to presentCommunity Guidance (PK).